Synthesis and study of properties of nanoparticles based on zinc oxide - A. Ya. Shalyapina; E. M. Hohlov; L. A. Polyakova; A. U. Soloveva (Тонкие химические технологии, 2011)
A chemical-technological process of preparing nano-sized zinc oxide as a shell of magnetite was developed. A comparative analysis of the size, shape, composition and spectral characteristics of ZnO nanoparticles in the initial dispersion and on the surface of Fe3O4 was carried out.